Response gene to complement 32 promotes tumorigenesis by mediating DNA damage repair and inhibits CD8+ T cells infiltration in diffuse large B-cell lymphoma - Zhang, Xiyuan; Lu, Tiange; Shi, Chunlei; Ding, Mengfei; Wang, Ling; Hu, Xinting; Wang, Xin (Frontiers in Immunology, 2025)
BackgroundResponse gene to complement 32 (RGC32), a complement activation-inducible factor broadly expressed in normal human tissues, has been implicated in tumorigenesis through its dysregulated expression in various malignancies and its involvement in critical oncogenic processes. Despite its established roles in cancer biology, RGC32 remains uncharacterized in diffuse large B-cell lymphoma (DLBCL). This study provides the first comprehensive investigation of RGC32 expression patterns and functional contributions to DLBCL pathogenesis, elucidating its potential as a novel therapeutic target or prognostic biomarker in this disease.MethodsImmunohistochemical (IHC) staining of RGC32 was performed on specimens from 32 Reactive hyperplasia lymphoid (RHL) patients and 80 DLBCL patients. To evaluate the role of RGC32 in DLBCL, lentivirus vectors either encoding shRGC32 or shControl were transfected into DLBCL cell lines. RNA-sequencing (RNA-seq) analysis was performed between shRGC32 and shControl stably transfected OCI-LY1 cells and functional enrichment analyses used gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG). In order to explored its functions in vivo, xenograft models were established by subcutaneously injecting shRGC32 and shControl transfected DLBCL cells into SCID beige mice.ResultsImmunohistochemical analysis revealed RGC32 overexpression in DLBCL tissues contrast with RHL, and was associated advanced Ann Arbor stage (p = 0.043), B symptoms (p = 0.020), and poor progression-free survival (p = 0.015) and overall survival (p = 0.035). Functional studies demonstrated that RGC32 knockdown via shRNA significantly suppressed DLBCL cell proliferation in vitro and in vivo, with xenograft models showing reduced tumor growth and Ki-67 expression. RNA-seq analysis linked RGC32 depletion to downregulation of cell proliferation and impaired DNA damage repair (DDR) mechanisms. Western blot showed RGC32 knockdown could suppress ATM/ATR/CHK1 pathway and increase the tumor mutational burden (TMB). Furthermore, after inhibition of RGC32, infiltration of CD8+ T cells was increased in DLBCL tumor microenvironment (TME).ConclusionsThis study highlights that RGC32 is a novel molecule in DLBCL progression and might be a potential therapeutic target for DLBCL therapy.